Analisis Pengaruh Harga dan Pendapatan Konsumen Terhadap Permintaan Handphone Pada Lingkup Karyawan - Hendri Andika Saputra; Dastanta Irvan Ginting; Dede Ruslan; Raina Linda Sari (Journal of Trends Economics and Accounting Research, 2023)
This research aims to conduct a comprehensive analysis of smartphone demand among employees. Employing an economic approach, the study seeks to explore the factors influencing the purchasing decisions of permanent employees at PT. CMS MAJU SEJAHTERA, utilizing a descriptive statistical analysis approach. The research sample consists of 65 permanent employees at PT. CMS MAJU SEJAHTERA, and variable measurements are conducted using a Likert scale (1 = strongly disagree; 5 = strongly agree). The research findings indicate that the demand for smartphones among permanent employees at PT. CMS MAJU SEJAHTERA is significantly influenced by income and price variables. Interestingly, the level of education did not prove to affect smartphone demand in this research context.